Geneflow 2009 - Bioversity International (2009)
Geneflow is Bioversity International’s flagship public awareness publication, now in its 20th year of production. The publication describes actions by local, national regional and international programmes to improve livelihoods and to conserve and use agricultural biodiversity around the world. Geneflow is distributed on an annual basis to approximately 6500 policymakers, media, donors and non-governmental agencies in about 120 countries. Geneflow always contains a special focus section devoted to a particular issue or area of work. This year Geneflow looks at two important topics: the Guardians of Diversity (Feature Section) and climate change (Special Report). Past issues of Geneflow have focused on women and biodiversity, crop wild relatives, on-farm conservation and botanic gardens.